Essentials of sport leadership theory and application - Megheirkouni, Majd; Norrington, Peter (Abingdon, Oxon ; New York, NY : Routledge, 2024)
This is a complete, stepbystep, readerfriendly introduction to leadership theories and their application in sport organizations. It outlines key concepts and approaches to leadership, clearly explains how they relate to sport, and shows how sport managers can use leadership theory to develop and improve their professional practice. This book covers leadership and management across all sectors of sport, including forprofit, nonprofit, and public, and adopts an international perspective that reflects the globalized reality of contemporary sport business. It explores key topics, including behavioural theories, transformational leadership, culture, selfleadership, ethics, and women in sport leadership, and encourages the reader to develop critical thinking skills that are essential in the modern workplace. Each chapter contains a selection of reallife examples, review questions, case studies, selfassessment exercises, topics for seminars and workshops, and suggested readings. This is an essential textbook for any sport leadership course, valuable reading for anybody with an interest in leadership theory or contemporary sport management, and a useful handbook for anybody working in sport or event management who wants to become a better manager. Online support material includes quizstyle questions and other resources for tutor use or adaptation.
Keywords: Sports administration; Leadership -- Philosophy; Human behavior -- Philosophy; Sports administration -- Research; SPORTS & RECREATION / General